2015
DOI: 10.2217/fvl.15.51
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bone Mineral Density Among ART-Naive Male Patients with HIV in China

Abstract: Authors contributed equally aims: To evaluate the prevalence and associated factors of reduced bone mineral density (BMD) among antiretroviral therapy (ART) naive HIV-infected male patients in China. Methods: We compared BMD between HIV-infected male patients and healthy controls. Risk factors of reduced BMD were studied using multivariable linear regression. Results: Reduced BMD rate of chronic HIV infection patients was higher. HIV infection was independently associated with decreased BMD after adjusting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…The above findings are consistent with the majority of published studies that have reported HIV‐1 to be an independent risk factor for low BMD ( 33‐37 ) and can be explained by the direct effect of the HIV‐1 virus, as well as chronic immune activation. In untreated HIV‐1, through direct viral effects and inflammatory effects, bone resorption and bone formation are uncoupled.…”
Section: Discussionsupporting
confidence: 91%
“…The above findings are consistent with the majority of published studies that have reported HIV‐1 to be an independent risk factor for low BMD ( 33‐37 ) and can be explained by the direct effect of the HIV‐1 virus, as well as chronic immune activation. In untreated HIV‐1, through direct viral effects and inflammatory effects, bone resorption and bone formation are uncoupled.…”
Section: Discussionsupporting
confidence: 91%
“…1 ). Data from both low-income countries such as Uganda [ 45 ▪ ], Nigeria [ 47 ▪ ], India [ 46 ], Indonesia [ 48 ] and middle-income countries (South Africa [ 49 ], Brazil [ 27 ], Turkey [ 50 ], China [ 51 , 52 ], Israel [ 53 ], and Thailand [ 54 ]) as well as mixed settings (South Africa, India, Thailand, Malaysia, and Argentina [ 55 ]) show varying levels of low BMD with some studies reporting a high prevalence of low BMD in HIV-positive individuals of up to 85% [ 53 ]. However, a few authors such as Hamill et al [ 49 ] from South Africa have reported comparable BMD levels between HIV-infected women and appropriate uninfected controls regardless of disease severity.…”
Section: Introductionmentioning
confidence: 99%